2019
DOI: 10.1002/stem.3107
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking the paradoxical endogenous stem cell response after spinal cord injury

Abstract: Nearly a century ago, the concept of the secondary injury in spinal cord trauma was first proposed to explain the complex cascade of molecular and cellular events leading to widespread neuronal and glial cell death after trauma. In recent years, it has been established that the ependymal region of the adult mammalian spinal cord contains a population of multipotent neural stem/progenitor cells (NSPCs) that are activated after spinal cord injury (SCI) and likely play a key role in endogenous repair and regenera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 57 publications
(123 reference statements)
0
16
0
Order By: Relevance
“…Altamentova and colleagues [57] demonstrated that methylprednisolone administered on P21, equivalent to a 2-year-old toddler and 14 days after hypoxia-ischemia on P7, provided durable improvement in both histology and gait through young adulthood (P56). While methylprednisolone reduces neuroinflammation, broad immunosuppression during development may have secondary unintended consequences [58][59][60], such as limiting the neurorestorative potential of the endogenous stem cell response that may be essential for replenishing lost neural cell progenitors [61]. Neuro-immunomodulation with endogenous neurorestorative hormones, such as EPO and MLT, may mitigate against unintended effects.…”
Section: Discussionmentioning
confidence: 99%
“…Altamentova and colleagues [57] demonstrated that methylprednisolone administered on P21, equivalent to a 2-year-old toddler and 14 days after hypoxia-ischemia on P7, provided durable improvement in both histology and gait through young adulthood (P56). While methylprednisolone reduces neuroinflammation, broad immunosuppression during development may have secondary unintended consequences [58][59][60], such as limiting the neurorestorative potential of the endogenous stem cell response that may be essential for replenishing lost neural cell progenitors [61]. Neuro-immunomodulation with endogenous neurorestorative hormones, such as EPO and MLT, may mitigate against unintended effects.…”
Section: Discussionmentioning
confidence: 99%
“…The in vivo direct lineage conversion and activation of endogenous NSCs is an alternative to the replacement of injured cells in the CNS. One approach applies recombinant cytokines to promote host tissue regeneration by stimulating endogenous stem cells pharmacologically (Lowry and Temple, 2007;Hachem et al, 2020). Alternatively the in vivo direct lineage conversion of somatic cells to neurons by forced expression of transcription factors could overcome endogenous NSC limitations.…”
Section: Clinical Challenges For Stem Cell-derived Graftsmentioning
confidence: 99%
“…However, here, ependymal cells (ECs) surrounding the central canal in the spinal cord express the same NSC markers as those in the SVZ, such as Sox2, Sox9 and CD133. Multipotent ECs are largely quiescent, proliferate at low rates, and generate few astrocytes and oligodendrocytes in healthy conditions (Hachem et al, 2020), indicating that spinal cord tissue is by default pro-gliogenic. EAE activates ECs, that besides predominantly generating astrocytes, also form OPCs that subsequently differentiate into myelinating oligodendrocytes (Meletis et al, 2008).…”
Section: Current Bottlenecks In Thyroid Hormone-mediated Repair In Mumentioning
confidence: 99%